Formyloxyacetoxyphenylmethane and 1, 1-diacylals as versatile O-formylating and O-acylating reagents for alcohols. Issue 44 (1st November 2018) - Chapman, Robert S.L.; Francis, Molly; Lawrence, Ruth; Tibbetts, Joshua D.; Bull, Steven D.
Abstract: Formyloxyacetoxyphenylmethane, symmetric 1, 1-diacylals and mixed 1-pivaloxy-1-acyloxy-1-phenylmethanes have been used as moisture stable O -formylating and O -acylating reagents for primary and secondary alcohols, allylic alcohols and phenols under solvent/catalyst free conditions to afford their corresponding esters in good yield. Graphical abstract: